Association of bone mineral density with prediabetes risk among African-American and European-American adult offspring of parents with type 2 diabetes - Liu, Zhao; Asuzu, Peace; Patel, Avnisha; Wan, Jim; Dagogo-Jack, Sam (Frontiers in Endocrinology, 2023)
Objectives: Type 2 diabetes mellitus (T2DM) is associated with alterations in bone mineral density (BMD), but association between prediabetes and BMD is unclear. Methods: We analyzed BMD among the initially normoglycemic participants in the Pathobiology of Prediabetes in a Biracial Cohort (POP-ABC) study in relation to incident prediabetes during 5 years of follow-up. Results: A total of 343 participants (193 Black, 150 White) underwent DEXA during Year 1 of POP-ABC and were followed quarterly for 5 years. The mean age was 44.2 ± 10.6 years; BMI was 30.2 ± 7.23 kg/m2. At baseline, the mean BMD was 1.176 ± 0.135 g/cm2 (1.230 ± 0.124 g/cm2 in men vs. 1.154 ± 0.134 g/cm2 in women, P<0.0001; 1.203 ± 0.114 g/cm2 in Black vs. 1.146 ± 0.150 g/cm2 in White participants, P=0.0003). During 5 years of follow-up, 101 participants developed prediabetes and 10 subjects developed T2DM (progressors); 232 were nonprogressors. Progressors to prediabetes had numerically higher baseline BMD and experienced lower 1-year decline in BMD (P<0.0001) compared with nonprogressors. From Kaplan-Meier analysis, the time to 50% prediabetes survival was 2.15 y among participants in the lowest quartile of baseline BMD, longer than those in higher quartiles (1.31 – 1.41 y). Values for BMD correlated inversely with age and adiponectin levels, and positively with BMI. In logistic regression analysis, BMD z score significantly predicted incident prediabetes: more negative BMD z scores were associated with decreased incident prediabetes (odds ratio 0.598 [95% confidence interval 0.407 - 0.877], P=0.0085), after controlling for age, BMI, change in BMI, ethnicity, blood glucose and adiponectin. Conclusions: Among initially normoglycemic individuals, higher baseline BMD was associated with higher risk of incident prediabetes during 5 years of follow-up.